2018
DOI: 10.1002/14651858.cd008218.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Anti-angiogenic therapy for high-grade glioma

Abstract: Analysis 2.1. Comparison 2 Anti-angiogenic therapy compared to no anti-angiogenic therapy for high-grade glioma (all patients, progression-free survival), Outcome

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
93
0
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 121 publications
(105 citation statements)
references
References 66 publications
0
93
0
12
Order By: Relevance
“…Although no studies of bevacizumab in patients with recurrent glioblastoma have demonstrated an improvement in survival, bevacizumab is FDA approved for the treatment of recurrent glioblastoma based on improvement in PFS. [162][163][164] Of note, improvement in PFS may be due to bevacizumab's ability to decrease BBB permeability (resulting in less contrast enhancement and vasogenic edema) rather than a true antitumor effect. 165,166 Treatment with regorafenib for recurrent glioblastoma is supported by the results of a randomized phase II trial in which OS was greater for patients randomized to receive regorafenib, compared with those who received lomustine (median OS of 7.4 months vs 5.6 months, respectively; HR, 0.50; 95% CI, 0.33-0.75; P,.001).…”
Section: Therapy For Recurrencementioning
confidence: 99%
“…Although no studies of bevacizumab in patients with recurrent glioblastoma have demonstrated an improvement in survival, bevacizumab is FDA approved for the treatment of recurrent glioblastoma based on improvement in PFS. [162][163][164] Of note, improvement in PFS may be due to bevacizumab's ability to decrease BBB permeability (resulting in less contrast enhancement and vasogenic edema) rather than a true antitumor effect. 165,166 Treatment with regorafenib for recurrent glioblastoma is supported by the results of a randomized phase II trial in which OS was greater for patients randomized to receive regorafenib, compared with those who received lomustine (median OS of 7.4 months vs 5.6 months, respectively; HR, 0.50; 95% CI, 0.33-0.75; P,.001).…”
Section: Therapy For Recurrencementioning
confidence: 99%
“…More recent phase 2 trial suggested that the combination of bevacizumab and lomustine did not confer a survival advantage over treatment with lomustine alone in patients with progressive GBM [139]. A randomized phase III trial in newly diagnosed GBM and recurrent grade III gliomas has failed to show an overall survival in [146,147]. These studies suggest that although a combination of anti-angiogenic therapy with chemotherapy compared with chemotherapy alone produces favorable results with improvements in objective response and PFS in patients with recurrent GBM, a large portion of the patients benefit because of a several factors including changes in the tumor microenvironment (TME) toxicity and resistance.…”
Section: Limitation Of Anti-vegf Therapy and Future Directionsmentioning
confidence: 99%
“…As studies performed on CT perfusion datasets seem to indicate that lower time resolution does not have a clinically significant impact on perfusion parameters [19,20], it remains to be seen if this holds true for MR perfusion. Wavelet-MRP might further be valuable in the assessment of therapy response to antivascular endothelial growth factor (VEGF) antibodies like bevacizumab [3,21,22]. The low patient number is one of the major study limitations.…”
Section: Neither Maximum Nor Mean Proliferation Correlate With Perfusmentioning
confidence: 99%